Le lussazioni traumatiche del ginocchio - Manca, M.; Isola, A.; D'Arcangelo, M.; Sirianni, R. (Lo Scalpello - Journal, 2018)
TRAUMATIC KNEE DISLOCATIONSKnee dislocations are rare and severe events. Their effects can be both acute, including extremely serious lesions of thevascular and nervous structures, and they may develop later, as a loss of function caused by damage to theligamentous structures. The diagnosis can be insidious if joint lesions recover spontaneously before the patient reachesobservation. Knowledge of the injury patterns and of the underlying traumatic mechanisms is therefore fundamentalto prevent missed or incomplete diagnoses. To date, the debate remains open on the treatment, timing, technique andselection of materials for reconstruction, but also on the ideal diagnostic pathway for vascular lesions. In this articlewe analysed the different aspects of the problem, highlighting the emerging trends from the most recent literature onthe subject.